Solitary wave solutions for a strain wave equation in a microstructured solid - Rehman, Hamood ur; Awan, Aziz Ullah; Habib, Azka; Gamaoun, Fehmi; Din, ElSayed M. Tag El; Galal, Ahmed M. (Results in physics, 2022)
In this article, a strain wave equation (SWE) is studied, which is used to model wave propagation in microstructured materials that earn a noteworthy place in solid-state physics. This equation also signifies the dynamics of various physical phenomena. The Sardar-subequation method (SSM) is utilized for this model. Granting appropriate values to parameters, we obtain various types of soliton solutions such as periodic singular solitons, bright solitons, dark solitons, singular soliton, combined dark-bright solitons, and some other wave solutions. These novel solitons and other wave results have significant applications in engineering and applied sciences. The graphical sketchings of the results are illustrated to purify the impact of the SSM. Furthermore, the executed technique can be utilized for further studies to discuss the realistic phenomena developing in physical and engineering problems. •A strain wave equation is studied, which is used to model wave propagation in microstructured materials.•The Sardar-subequation method is utilized for this model.•Granting appropriate values to parameters, we obtained various types of soliton solutions.•These novel solitons and other wave results have significant applications in engineering and applied sciences.